Pengaruh Kompetensi, Independensi Dan Pengalaman Kerja Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderasi Studi Empiris pada Kantor Akuntan Publik di Surakarta dan Yogyakarta - Saputra, Surya Aji; , Fauzan, S.E, M.Si, Akt, CA (2016)
The objectives of this research to empirically analyze the influence of competency, independency, work experience on audit quality, and to the influence of competency, independency and work experience to audit quality is moderated by auditor ethics, especially on auditors working on a public accountant office in the region of Surakarta and Yogyakarta. The population in this research are all auditors who worked on the public accountant office in the region of Surakarta and Yogyakarta. Sampling was conducted using a purposive sampling method and number of samples of 69 respondents. Primary data collection method used is questionnaire method. The data are analyzed by using technical analyze Moderate Regression Analyze (MRA). The results showed that the effect on the competence and independence of audit quality, whereas work experience had no effect on audit quality. Interaction competence and ethics of auditors, ethics and auditor independence interaction effect on audit quality, while the interaction of work experience and ethical auditor has no effect on audit quality. Value of the coefficient of determination indicates that together the competency, independency, work experience and Auditors Ethics contribute to dependent variable (quality audit) of 93,2% while the remaining 6,8% are influenced by other outside factor model.